Evaluasi Efektivitas Penggunaan Kurikulum 2013 dan Merdeka Dalam Pendidikan di UPT SDN 064037 Medan Tembung - Harahap, Putri Hasanah; Fadilla, Putri Amanda; Kesuma, Bunga; Salsabila, Nadia; Maibang, Sapriani; A, Aufa (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research aims to explore the effectiveness of implementing the 2013 Curriculum (K-13) and the Independent Curriculum at UPT SD Negeri 064037 through in-depth interviews with a senior teacher. Interviews will be held on Monday, May 6 2024, starting at 9 o'clock until the end. The research subjects were teachers at the school who had experience teaching with both curricula. Research procedures include preparing a list of interview questions, conducting interviews using recording equipment, and analyzing interview data. The instruments used are a list of questions and recording tools to ensure that the data is obtained completely and accurately. Data collection techniques were carried out using in-depth interviews, while data analysis techniques involved transcription, coding and thematic analysis. The results of the interview show that this school uses two curricula, namely the Merdeka Curriculum for grades 1 and 4 and K-13 for grades 2, 3 and 5. The teachers interviewed stated that the Merdeka Curriculum makes the learning process easier because it is centered on students and adapts to their needs. However, there are challenges in implementing the Independent Curriculum, especially in maintaining student etiquette. The teacher also revealed that the Independent Curriculum was easier for students to accept because it provided freedom in learning methods. Even so, frequent changes to the curriculum raise hopes that there will be stability in the implementation of the curriculum in the future. Overall, implementation of the Merdeka Curriculum in this school reaches around 40%, with some teachers combining elements from both curricula to improve students' skills and creativity.